Analysis of Perceptual Expertise in Radiology – Current Knowledge and a New Perspective - Waite, Stephen; Grigorian, Arkadij; Alexander, Robert G.; Macknik, Stephen L.; Carrasco, Marisa; Heeger, David J.; Martinez-Conde, Susana (Frontiers in Human Neuroscience, 2019)
Radiologists rely principally on visual inspection to detect, describe, and classify findings in medical images. As most interpretive errors in radiology are perceptual in nature, understanding the path to radiologic expertise during image analysis is essential to educate future generations of radiologists. We review the perceptual tasks and challenges in radiologic diagnosis, discuss models of radiologic image perception, consider the application of perceptual learning methods in medical training, and suggest a new approach to understanding perceptional expertise. Specific principled enhancements to educational practices in radiology promise to deepen perceptual expertise among radiologists with the goal of improving training and reducing medical error.